PROBIOTIC DEVELOPMENT OF ACID BACTERIA OF LUBRICATED POTENTIAL WASTE REDUCING CHICAGEN CHOLESTEROL BEHAVIOR BROILER STRAIN HABBART - Astuti Astuti (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2010)
The aims of rhis research is to .\/reptococcus thermophillus .from .fintl thc in.fluence of gifing lsctlate probiotic B,4L The.fish waste trn'ard the broilers' cind the degree Oj bt